PARTICIPATORY PLANNING AND BUDGETING THROUGH BOURDIEU THEORY PERSPECTIVE - Galuh Tiaramurti (Robust: Research of Business and Economics Studies, 2023)
Village funds are obtained from a participatory planning and budgeting process that occurs before the end of the fiscal year. Fourteen districts in Indonesia have not yet finalized local regulations regarding the distribution of village funds. Problems in the district, including the habit of the village government waiting for the funding of the central government for village funds, also because the village does not implement a good participatory budget, because the capabilities of village officials and their own residents are not sufficient. The purpose of this study is to analyze more deeply the culture of participatory planning and budgeting with a bourdieu perspective in Pule Village, Sawahan District. The village that received the Smallest Village Fund in Madiun Regency. This study uses a qualitative approach with ethnographic methods from the perspective of Bourdieu. Bourdieu's theory is used as a grand theory in the preparation of a public policy. The results of the study prove that the Pule Village Community is very critical so that the planning and budgeting process is carried out in a more democratic and participatory manner.